SPECTRAL TYPE AND RADIAL VELOCITY VARIATIONS IN THREE SRC VARIABLES - Moncrieff, K. E.; Turner, D. G.; Short, C. I.; Bennett, P. D.; Balam, D. D.; Griffin, R. F. (Одеські астрономічні публікації, 2010)
SRC variables are M supergiants, precursors to Type II supernovae, that vary in brightness with moderately regular periods of order 100–1000 days. Although identified as pulsating stars that obey their own period-luminosity relation, few have been examined in enough detail to follow the temperature and spectral changes that they undergo during their long cycles. The present study examines such changes for several SRC variables revealed by CCD spectra obtained at the Dominion Astrophysical Observatory (DAO) during 2005–2009, as well as by archival spectra from the DAO (and elsewhere) for some stars from the 1960s to 1980s, and Cambridge radial velocity spectrometer measures for Betelgeuse. Described here is our classification procedure and information on the spectral type and radial velocity changes in three of the stars. The results provide insights into the pulsation mechanism in M supergiants.